2020
DOI: 10.31951/2658-3518-2020-a-4-1000
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic oxidation of methane in differences types of geological structures at Lake Baikal

Abstract: Although in sediments of Lake Baikal process of anaerobic oxidation methane was revealed by radioisotope techniques, by of the methane profile we know a little about the microorganisms carrying out this process. Here we studied diversity of archaeal communities in different types geological structures (methane seeps and mud volcano) on Lake Baikal with different composition of pore waters and the discharged fluid. In investigate were used different methods molecular biology including of high-throughput sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Methane and its homologues associated with gas hydrates of the MV Kedr have a thermogenic or secondary-microbial genesis that differs from the other hydrate-bearing zones of the lake due to the active biodegradation processes. These data are consistent with the presence of molecular markers of anaerobic methanotrophic archaea in sediments [49].…”
Section: Geological Setting Of Lake Baikal Sampling Sitessupporting
confidence: 90%
See 4 more Smart Citations
“…Methane and its homologues associated with gas hydrates of the MV Kedr have a thermogenic or secondary-microbial genesis that differs from the other hydrate-bearing zones of the lake due to the active biodegradation processes. These data are consistent with the presence of molecular markers of anaerobic methanotrophic archaea in sediments [49].…”
Section: Geological Setting Of Lake Baikal Sampling Sitessupporting
confidence: 90%
“…The study of the southern basin included the sampling of sediments from the mud volcano Malenky (site 13, Figure 1, Table 1; [6,7,13,28,[48][49][50]) and gas hydrate-bearing sediments from the mud volcano Kedr (site 14, 15, Figure 1, Table 1; [49,51,52]). The former study of gas fluid from the MV Malenky [6] has suggested its possible migration from the deep strata.…”
Section: Geological Setting Of Lake Baikal Sampling Sitesmentioning
confidence: 99%
See 3 more Smart Citations